(untitled) (Baghdad Science Journal, 2022)
This study was undertaken to introduce a fast, accurate, selective, simple and environment-friendly colorimetric method to determine iron (II) concentration in different lipstick brands imported or manufactured locally in Baghdad, Iraq. The samples were collected from 500-Iraqi dinars stores to establish routine tests using the spectrophotometric method and compared with a new microfluidic paper-based analytical device (µPAD) platform as an alternative to cost-effective conventional instrumentation such as Atomic Absorption Spectroscopy (AAS). This method depends on the reaction between iron (II) with iron(II) selective chelator 1, 10-phenanthroline(phen) in the presence of reducing agent hydroxylamine (HOA) and sodium acetate (NaOAc) buffer to yield a reddish/orange colour change proportional to the iron(II) concentration measured at λmax = 510 nm. Under optimum conditions, the calibration curve was linear in the range between (0.5-150) mg L-1 with a limit of detection of 0.09 mg L-1. Compared to a spectrophotometric detection method, µPAD measured colour intensity using captured images using Samsung mobile phone and image J program to give proof of concept that µPAD platform fulfils the purpose of accuracy and at the same time remaining cost-effective and simplistic to be used in both developing and developed countries gave same linear calibration curve with a limit of detection 0.12 mg L-1. ANOVA test was used to compare the proposed method results with conventional method results showing the method was accepted. The antimicrobial activity showed no significant effect from lipstick samples on tested microbes.